Factors Affecting The Decisions Of Local People To Participate In Community Tourism In The NorthWest of Vietnam - HUONG, NGUYEN THI QUYNH; NHAN, BUI XUAN; HUY, DINH TRAN NGOC; TU, NGUYEN THI (The journal of contemporary issues in business and government, 2021)
This paper aims to find out factors affecting decision making to join in community tourism via qualitative (analysis, synthesis) and quantitative methods. The Northwest of Vietnam is regarded as a region with sufficient and favorable conditions to develop community tourism. Accordingly, determining what factors affect the decisions of local people to participate in community tourism is of great significance in developing tourism and raising the competitiveness of tourism destinations in this region. On the basis of the collected primary and secondary data, the research paper has identified 4 factors affecting the decisions of local people to participate in community tourism, including: (1) Personal factors, (2) Attractiveness and images of tourism destinations in the Northwest, (3) Supports and investments from the State, local authorities, organization and enterprises in the Northwest, (4) Effects from people around; then proposed solutions to attract local people to participate in community tourism and develop this form of tourism sustainably in the Northwest of Vietnam in the coming time. For instance, we need to exploit the beauty of natural scenes of Nowthwestern mountains, forest and lakes with local attributes to reform a better community tourism in this region.